2022
DOI: 10.3390/jfb13040258
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Medical Grade Resin with Enhanced Mechanical and Antibacterial Properties: The Effect of Copper Nano-Inclusions in Vat Polymerization (VPP) Additive Manufacturing

Abstract: Vat photopolymerization (VPP) is an additive manufacturing process commonly used in medical applications. This work aims, for the first time in the literature, to extend and enhance the performance of a commercial medical-grade resin for the VPP process, with the development of nanocomposites, using Copper (Cu) nanoparticles as the additive at two different concentrations. The addition of the Cu nanoparticles was expected to enhance the mechanical properties of the resin and to enable biocidal properties on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 116 publications
(146 reference statements)
0
2
0
Order By: Relevance
“…As for the additive manufacturing of metal-filled plastic materials, for example, resins with copper nano-inclusions were used with the VAT-polymerization (VPP) technique in a work by Vidakis et al [14]. They found that adding 0.5 wt.…”
Section: Introductionmentioning
confidence: 99%
“…As for the additive manufacturing of metal-filled plastic materials, for example, resins with copper nano-inclusions were used with the VAT-polymerization (VPP) technique in a work by Vidakis et al [14]. They found that adding 0.5 wt.…”
Section: Introductionmentioning
confidence: 99%
“…However, standard resins used in VPP printing result in printouts with poor mechanical properties that are unsuitable for structural applications. Consequently, efforts have been made to improve mechanical behavior by reinforcing the cured resins with additional phases, leading to the development of polymeric matrix composites [2,[4][5][6]. Nanofillers play a crucial role in reinforcing the matrix due to their high specific surface area, which creates a strong interphase with the matrix [6].…”
Section: Introductionmentioning
confidence: 99%